Assessment of Occupational Health Hazards Among Oil Refinery Workers at Kaduna Refining and Petrochemical Company - ABDULRASAK, Raji; ALIYU, Abdulaziz S. (FUDMA Journal of Engineering and Technology, 2026)
Occupational health and safety are vital in the petroleum refining industry due to various hazards faced by workers. A study at Kaduna Refining and Petrochemical Company (KRPC) evaluated industrial accidents and preventive measures using a survey of 250 employees. A cross-sectional survey design was adopted, while primary data were utilized. Structured questionnaires were administered to 250 employees selected from a population of 1,696 workers using the Yamane sampling formula and simple random sampling technique, frequency and percentage was used for the demographic items while mean and standard deviation with remarks was used for the research questions. Findings indicated a relatively low perception of industrial hazards (mean score 2.21), although work-related deaths raised significant concern (mean score 3.06). Positive acknowledgment was given to safety measures like personal protective equipment and hazard management systems (mean score 3.96). Based on these survey results, the study concludes that KRPC staff perceive several safety measures in place but recommends further investigation using objective environmental monitoring and enforcement/audit records to verify exposure and compliance.
Keywords: Occupational health, industrial accidents, refinery workers, workplace safety, KRPC.